The Old Iron Road An Epic of Rails, Roads, and the Urge to Go West. - Bain, David Haward (Bison Books, 2022)
A combination of travelogue, history, and storytelling, this is the story of David Haward Bain's family's travels from their home in Vermont to the West in search of America's past.